Analysis of Implementation â€œTeacher Redistributionâ€ Policy to Improve Education Quality in Elementary School (Study on Office of Education and Regional Employment Board of Ngawi Regency) - Mey Meliana Sari (Jurnal Administrasi Publik, 2015)
Abstrak: Analisis Implementasi Kebijakan Redistribusi Guru Terhadap Peningkatan Kualitas Sekolah Dasar (Studi Di Dinas Pendidikan Dan Badan Kepegawaian Daerah Kabupaten Ngawi). Pembahasan tentang pendidikan tidak akan habisnya diperbincangkan dari era ke era. Perkembangan jaman yang semakin pesat mengakibatkan pula kebijakan mengenai pendidikan di Indonesia terus diperbaharui. Salah satu kebijakan yang dikeluarkan di akhir tahun 2011 adalah Redistribusi Guru dalam SKB Lima Menteri untuk mengatasi permasalahan ketimpangan jumlah guru yang ada di satuan pendidikan. Kabupaten Ngawi adalah salah satu daerah yang mengimplementasikan kebijakan tersebut di mana jumlah guru di SD kurang sementara jumlah guru SMP dan SMA lebih. Maka dari itu pemerintah daerah memutasi guru SMP dan SMA menjadi guru SD. Hasil penelitian ini menemukan bahwa peningkatan kualitas sekolah dasar di SDN Jatimulyo 1 dan SDN Pakah 3 Kecamatan Mantingan dapat berjalan stabil dan mengalami peningkatan, walaupun begitu ada permasalahan mengenai kesejahteraan guru dalam sertifikasi ulang. Selain itu, implementasi kebijakan juga berjalan dengan baik, tetapi terdapat permasalahan terkait kepatuhan dan respon yang ditimbulkan sehingga menghambat pelaksanaan kebijakan tersebut. Kata Kunci: Implementasi Kebijakan, Pendidikan, Redistribusi Guru, Kualitas Sekolah Dasar Abstract: Analysis Of Implementation â€œTeacher Redistributionâ€ Policy To Improve Education Quality In Elementary School (Study on Office Of Education and Regional Employment Board of Ngawi Regency). Education is and will be a timeless topic for discussion from time to time as it continues to grow along with the development of science and technology. It resulting also to the policy on education of Indonesia continuously updated. One of the policies issued at the end of 2011 was Teacher Redistribution signed by Joint Decree of Five Ministries to tackle the problem of unequal number of teachers across cities. Ngawi Regency was one of the regions that implemented the policy in which the number of teachers in Elementary Schools was less, while the number of junior and senior high school teachers was more. Thus, the local government transferred a number of junior and senior high school teachers into elementary schools. The results of the study shows that the improvement the quality of elementary schools at SDN Jatimulyo 1 and SDN Pakah 3 of Mantingan District that can run stable and increasing, regardless the fact that there is a problem concerning the welfare of the teachers in the recertification. Moreover, its implementation goes well; yet, there are problems related to compliance and responsiveness of mutated teachers, thus hampering the implementation of the policy. Â  Keyword: Policy Implementation, Education, Redistribution Teacher, Quality of Elementary School Â